Contradictive Istinbath Akad Murabahah Law Bil of Sharia Financing Time - nurhadi, nurhadi (Li Falah: Journal of Islamic Economics and Business, 2019)
A contract is a written agreement between a Sharia Bank or a Sharia Business Unit and another party that contains the obligation for parties in accordance with sharia principles, this is a definition according to the Sharia Banking Law. A contract is a legal relationship between parties that creates rights and obligations that are exchanged by the parties. An agreement is an event someone promises to another person or somewhere two people promise to do something or plan. All three are equated in the concept of business law engagement. The difference between the agreement and the contract according to the science of jurisprudence, the agreement is different from the agreement according to business law, but the difference is only in the term of use. By law and sharia, the murabahah and wakalah contracts are legalized. But if the murabahah bil wakalah agreement is not clear between the two contracts which one is used, there is obscurity (gharar), the law is haraam. But if the two contracts can be clear (not gharar) and separate (which one is the right one), then a transaction with two contracts is permitted, for example murabahah bil wakalah transaction, by means of the wakalah contract, then the murabahah contract, then this contract is enforced.